Cost-effective assembly of the African wild dog (Lycaon pictus) genome using linked reads. Issue 2 (22nd October 2018) - Armstrong, Ellie E; Taylor, Ryan W; Prost, Stefan; Blinston, Peter; van der Meer, Esther; Madzikanda, Hillary; Mufute, Olivia; Mandisodza-Chikerema, Roseline; Stuelpnagel, John; Sillero-Zubiri, Claudio; Petrov, Dmitri
Abstract: Background: A high-quality reference genome assembly is a valuable tool for the study of non-model organisms. Genomic techniques can provide important insights about past population sizes and local adaptation and can aid in the development of breeding management plans. This information is important for fields such as conservation genetics, where endangered species require critical and immediate attention. However, funding for genomic-based methods can be sparse for conservation projects, as costs for general species management can consume budgets. Findings: Here, we report the generation of high-quality reference genomes for the African wild dog ( Lycaon pictus ) at a low cost (<$3000), thereby facilitating future studies of this endangered canid. We generated assemblies for three individuals using the linked-read 10x Genomics Chromium system. The most continuous assembly had a scaffold and contig N50 of 21 Mb and 83 Kb, respectively, and completely reconstructed 95% of a set of conserved mammalian genes. Additionally, we estimate the heterozygosity and demographic history of African wild dogs, revealing that although they have historically low effective population sizes, heterozygosity remains high. Conclusions: We show that 10x Genomics Chromium data can be used to effectively generate high-quality genomes from Illumina short-read data of intermediate coverage (∼25x–50x). Interestingly, the wild dog shows higher heterozygosity than other species of conservation concern, possibly due to its behavioral ecology. The availability of reference genomes for non-model organisms will facilitate better genetic monitoring of threatened species such as the African wild dog and help conservationists to better understand the ecology and adaptability of those species in a changing environment.